(untitled) (Scientific journal of the Fergana State University, 2023)
The role of Zahiriddin Muhammad Babur’s "Boburnoma" in reflecting the formation and improvement of the cultural, social and political life of Eastern Khurasan is immense. This historical masterpiece not only embodies and recounts the past stories of the people, but as a literary work, it has left an effective role in the formation and development of Uzbek classical literature. In this article, the authors of Persian verses that are not mentioned in "Baburnoma" and some errors of these verses are studied and researched.